Simulation modelling of public-private partnership in the Arctic regions - Tarasova, Olga (Louvain-la-Neuve: European Regional Science Association (ERSA), 2016)
Arctic vector of economic development is now a strategic imperative for the Russian Federation. Apparently, severe climatic conditions, low population density, lack of infrastructure leave all Arctic projects outside the market and allow only nodular economic development of the Russian Arctic territories. The internal structure of these patches of economic activity should be justified with the help of economic-mathematical modeling. This becomes of particular importance given that all Arctic investment projects will for sure employ administrative and financial resources of the state along with private initiative. Views on state participation in the economy are different: from the invisible hand of Adam Smith's market to a tight state policy of Soviet administrative economy. On the other hand, it is impossible to use templates in the Russian Arctic: PPP best practices might not give results in risky northern conditions. Each group of projects should be simulated and all effects forecasted on the series of evaluative scenario calculations. Certain results in this direction have been obtained and described by the authors in previous works. The aim of the present work was to search for opportunities as well as to implement modifications of economic-mathematical models used for the assessment in order to improve the convenience of predictive scenario calculations and expand the analytical capabilities of instruments. The simulation model was modified in the following areas: 1. introduced an opportunity to observe the project's effects in dynamics. It is important when choosing a combination of measures of state support when taking into account the correlation of their effectiveness in various stages of implementation; 2. added a variability of projects' productivity; 3. added an option to specify the result year (up to which a forecast of the development ought to be done, and accordingly, all effects to be shown). The idea was that for different actors of the project different length of the forecast period could be ...